Hyperfine and magnetic properties of a YxLa1-xFeO3 series (0<x<1) - Cristobal, Adrian Alberto (2015)
A series of orthoferrites YxLa1-xFeO3 in the entire range of composition was synthesized at room temperature by mechanochemical activation of oxide mixtures. Phase composition, structure and microstructure of the obtained powder materials were characterized by X-ray diffraction and field-emission scanning electron microscopy. Hyperfine interactions and magnetic properties were determined by Mössbauer spectroscopy, SQUID and vibrating sample magnetometry. Two magnetic contributions could be identified in the series of materials: a paramagnetic state, associated with a fraction of the smallest particles and a ferromagnetic state, attributed to the larger particles. The results showed that the relative proportion of both contributions is very dependent on x, the Y content of samples. From M vs T measurements, it was possible to estimate the blocking temperature distribution for the end members of the series. Annealing of samples produced the elimination of the superparamagnetic behavior and the formation of Y3Fe5O12 impurities.